2017
DOI: 10.1002/aenm.201602610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Charge Transport and Defects on the Performance of Planar and Mesostructured Perovskite Solar Cells

Abstract: describing charge transport are the carrier mobility, charge generation/extraction, and carrier lifetime observed in fully assembled, operating solar cells. [5] There are several well-known experimental approaches toward estimation of these parameters including time-of-flight (TOF) photoconductivity, [6] space charge limited current (SCLC), [7] field-effect transistor (FET), [8] and charge extraction by linearly increasing voltage (CELIV). [9,10] However, each of them is hindered by an array of limitations. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…56,57 Moreover, we note the absence of any apparent charge reservoir, as this occurrence would enhance the random-walk mechanism during the carrier transport and cause a decay trend of higher orders. 58,59 As mentioned earlier, all transient decays in our case exhibited a mono-exponential trend which is not indicative of any effectual accumulation of charge carriers. 60 The full set of TPV transients taken at each step of UV degradation is given in the ESI (Fig.…”
Section: Resultssupporting
confidence: 66%
“…56,57 Moreover, we note the absence of any apparent charge reservoir, as this occurrence would enhance the random-walk mechanism during the carrier transport and cause a decay trend of higher orders. 58,59 As mentioned earlier, all transient decays in our case exhibited a mono-exponential trend which is not indicative of any effectual accumulation of charge carriers. 60 The full set of TPV transients taken at each step of UV degradation is given in the ESI (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Similarly, by modified photo-CELIV, nondispersive electron transport was also observed in planar MAPbI 3 solar cells caused by the passivating function of PCBM, while dispersive electron transport was clearly observed in mesoporous perovskite devices due to the presence of traps at the TiO 2 / MAPbI 3 interface. 27 This work further emphasized the importance of the PCBM layer in achieving a nondispersive nature in perovskite devices.…”
Section: View Article Onlinementioning
confidence: 85%
“…More recently, a modified photo-CELIV method was taken to separately measure the hole and electron mobilities of perovskites by inserting a 100 nm-thick MoO 3 layer in front of the selected electrodes to block the unwanted type of carrier. 27 To uncover the effect of the device structure on transport dynamics, mesoporous and inverted planar MAPbI 3 devices were comparatively investigated as shown in Fig. 3C.…”
Section: Devices With Electrodesmentioning
confidence: 99%
“…However, the instability of perovskite absorber materials (Correa-Baena et al, 2017) and difficulty in large area fabrication devices (Li et al, 2018b) is still serious problems for future commercialization of p e r o v s k i t e -b a s e d s o l a r c e l l . So far, the planar n-i-p structured PSCs (Halvani Anaraki et al, 2018;Yang et al, 2018a) shows great promise due to their easier upscaling deposition of electron transport layers (ETLs) compared to mesostructured PSCs (Petrović et al, 2017). And there are lots of fabrication methods (Chen et al, 2019) have been reported to efficiently deposit thin ETL films, however, not all the methods are suitable for achieving uniform large area high quality thin films for large area perovskite solar modules (PSMs).…”
Section: Introductionmentioning
confidence: 99%